2013
DOI: 10.1371/journal.pone.0058515
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Isomerization and Inversion of Aspartate 58 of αA-Crystallin Peptide Mimics under Physiological Conditions

Abstract: Although proteins consist exclusively of L-amino acids, we have reported that aspartyl (Asp) 58 and Asp 151 residues of αA-crystallin of eye lenses from elderly cataract donors are highly inverted and isomerized to D-β, D-α and L-β-Asp residues through succinimide intermediates. Of these Asp isomers, large amounts of D-β- and L-β-isomers are present but the amount of D-α-isomer is not significant. The difference in abundance of the Asp isomers in the protein may be due to the rate constants for the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 25 publications
(28 reference statements)
7
40
0
Order By: Relevance
“…This is due to the well-known succinimide-mediated mechanism [12][13][14][15]. In this mechanism, the actual species undergoing racemization is a succinimide intermediate which is formed from an L-Asp residue by an intramolecular cyclization with the loss of a water molecule.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the well-known succinimide-mediated mechanism [12][13][14][15]. In this mechanism, the actual species undergoing racemization is a succinimide intermediate which is formed from an L-Asp residue by an intramolecular cyclization with the loss of a water molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Normal L-α-Asp decreases to less than 10% of the total Asp content within the first 5.5 years of life, whereas L-β-Asp markedly increases to 90% and then decreases gradually. D-β-Asp increases gradually, reaching approximately 30% of Asp content at 82 years [36]. Hooi et al previously reported that Asp 151 of αA-crystallin converts to the D-β-, L-β-, and D-α-isomers in a ratio of 3:1:0.5 until 15 years of age; in addition, 40% of Asp 151 is present as the D-β-isomer by 20 years, and this proportion remains fixed until 80 years [39].…”
Section: Mechanism Underlying the Spontaneous Isomerization Of Asp Rementioning
confidence: 99%
“…The rate constants k2, k4, k6, k8, k9 and k10 were obtained by heating the L-succinimidyl-and D-succinimidylcontaining peptides at 37°C for 80 min. The rate constants for k1-k10 were calculated by fitting curves of the relative amount of reaction products vs time [36].…”
Section: Mechanism Underlying the Spontaneous Isomerization Of Asp Rementioning
confidence: 99%
“…However, D-aspartyl (Asp) residues have been found in aged lens [1][2][3][4], tooth [5], aorta [6], brain [7,8], bone [9,10], and ligament [11]. D-Asp is produced Biophysical Chemistry 196 (2015) [10][11][12][13][14][15] by the racemization of natural L-Asp residues in the protein. The racemization is accompanied by the isomerization from the natural α-Asp to the uncommon β-Asp form via a succinimide intermediate [12].…”
Section: Introductionmentioning
confidence: 99%
“…For the racemization, the formation of succinimide is thought to be the rate-determining step [13,14]. Previous studies have suggested that β-Asp is more stable than α-Asp in humanlens αA-crystallin peptides [14].…”
Section: Introductionmentioning
confidence: 99%